(3GddHGH aj JgPjH GdCfSGHs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfqj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ , J (B630 (3g`s; (3YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efgG ef MQa GdQGA HGH GdQGA hGdCda bhdg (B: (3GdQGRGfi HaJM GdQGA hSchf GdCda haJM GdRGi s
(3BNQgG (B:s
(3abGd Efg djbQeW ai eTjg bGdg eMeO Hf WGgQ GdebOSi GdbQejSjfi Je GdLRA GdChd GdeHGQc jJdhg ai GdLRA GdKGfi GdPi jdjg GdbQejSjfi s
(3fSNI KGfjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3JYGhQ YdjgG CcKQ ef fGSN hHgG HYV GdfbU hJbWjY hHgG eTgG JbjjOGJ egeI hgj ef hba GdeOQSI GdCTQajIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs